Evolution of Helium Bubbles and Discs in Irradiated 6H-SiC during Post-Implantation Annealing - Qiang Shen (Materials, 2017)
The single crystal 6H-SiC with [0001] crystal direction irradiated by 400 keV He+ ions with 1 × 1017 ions/cm2 fluence at 400 °C were annealed at 600, 900, 1200 and 1400 °C for different durations. The evolution of helium bubbles and discs was investigated by transmission electron microscopy. An irradiated layer distributed with fine helium bubbles was formed with a width of ~170 nm after helium ion irradiation. The size of gas bubbles increased with increasing annealing time and temperature and finally reached stable values at a given annealing temperature. According to the relationship between the bubble radii and annealing time, an empirical formula for calculating the bubble radii at the annealing temperature ranged from 600 to 1400 °C was given by fitting the experiment data. Planar bubble clusters (discs) were found to form on (0001) crystal plane at both sides of the bubble layer when the annealing temperature was at the range of 800–1200 °C. The mechanism of bubble growth during post-implantation annealing and the formation of bubble discs were also analyzed and discussed.